Pendampingan Belajar Baca Tulis Pegon bagi Santri Baru MTs di Pondok Pesantren Al-Amien Ngasinan Rejomulyo Kediri - Mahmudah Fitriani Ningrum, Siti; Syamsudin, Ahmad (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
Islamic boarding schools have a variety of learning methods used in educating their students, both of formal and non-formal education. In addition, Islamic boarding schools also have a curriculum that mostly uses the yellow book, bald and without vowels, so it takes a long time and serious effort to really understand it. There are many sciences that must be passed, starting from writing, reading and even translating. Therefore, there are many scholars who make scientific contributions to come up with easy methods so that students can use them well. One of them is the publication of a small and simple book, namely the Pegon Book, which is a small book that provides the instructions and guidance on writing Arabic letters in Javanese (pegon) in a method that is easily understood by new students. This study aims to improve the literacy skills of new students who are still unfamiliar with Pegon. To achieve the above objectives, researchers used descriptive qualitative research methods, which is a method to describe the collected data clearly and in detail as they are. While the data collection techniques using observation, interviews and documentation as well as data sources that come from boarding school administrators and researchers themselves who go directly to the field. The results of this study indicate that students can write, read, interpret, and understand the yellow book in Arabic without vowels properly and correctly.